Pre-birth acquisition of personhood: Incremental accrual of attributes as the framework for individualization by serial and concurrently acting developmental factors - Hughes, Claude L.; Hughes, Gavin C. (Frontiers in Reproductive Health, 2023)
Discrete events and processes influence development of individual humans. Attribution of personhood to any individual human being cannot be disconnected from the underlying biological events and processes of early human development. Nonetheless, the philosophical, sociological and legal components that are integral to the meaning of the term as commonly used cannot be deduced from biology alone. The challenge for biomedical scientists to inform discussion in this arena then rests on profiling the key biological events and processes that must be assessed when considering how one might objectively reason about the task of superimposing the concept of personhood onto the developing biological entity of a potential human being. Endogenous genetic and epigenetic events and exogenous developmental milieu processes diversify developmental trajectories of potential individual humans prior to livebirth. First, fertilization and epigenetic resetting of each individual's organismic clock to time zero (t = 0) at the gastrulation/primitive streak stage (day 15 of embryogenesis), are two discrete unseen biological events that impact a potential individual human's attributes. Second, those two discrete unseen biological events are immersed in the continuous developmental process spanning pre-fertilization and gestation, further driving individualization of diverse attributes of each future human before the third discrete and blatant biological event of parturition and livebirth. Exposures of the gravida to multiple diverse exogenous exposures means that morphogenesis and physiogenesis of every embryo/fetus has individualized attributes for its future human lifespan. Our proposed framework based on the biological discrete events and processes spanning pre-fertilization and prenatal development, implies that personhood should be incrementally attributed, and societal protections should be graduated and applied progressively across the pre-birth timespan.